Long-lived Paleoproterozoic eclogitic lower crust - Sebastian Buntin (Nature Portfolio, 2021)
The nature of the lower crust and the crust-mantle transition is fundamental to Earth Sciences. Here, the authors provide evidence for long-lasting presence of lower crustal eclogite below the seismic Moho, challenging conventional models.